Stunting Training For Women With Toddlers - Gani, H. Abdul; Elviani, Yeni; Detiana; Kamestworo (Journal of Applied Nursing and Health, 2023)
Background: Stunting, a prevalent nutritional issue in Indonesia, significantly affects cognitive abilities and long-term productivity. Age, defined as the duration of a person's existence, is essential in assessing anatomical and physiological development. In this context, rheumatic gymnastics aids in the healing process. Methods: The practice of body movement in rheumatic gymnastics serves as an effective measure in lowering the likelihood of developing rheumatism. Moreover, it is a therapeutic approach to alleviate symptoms like stiffness and joint pain experienced by individuals with rheumatism. Another approach to tackling stunting in toddlers is counselling on proper nutrition and enhancing feeding skills. Empowering mothers with toddlers encourages the community to take independent action to prevent health issues. This community empowerment is crucial in promoting proactive measures for maintaining good health. Results: These results showed that before the training was carried out, there were 20 mothers who had toddlers who did not know about stunting. After counselling and training on stunting, as many as 20 elderly people were able to practice additional food processing skills for toddlers. Conclusion: Stunting training is very useful, and the training model needs to be developed for parents, especially mothers